Advances in Surface Plasmon Resonance Imaging and Microscopy and Their Biological Applications - Bocková, Markéta; Slabý, Jiří; Špringer, Tomáš; Homola, Jiří (Annual review of analytical chemistry, 2019)
Surface plasmon resonance microscopy and imaging are optical methods that enable observation and quantification of interactions of nano- and microscale objects near a metal surface in a temporally and spatially resolved manner. This review describes the principles of surface plasmon resonance microscopy and imaging and discusses recent advances in these methods, in particular, in optical platforms and functional coatings. In addition, the biological applications of these methods are reviewed. These include the detection of a broad variety of analytes (nucleic acids, proteins, bacteria), the investigation of biological systems (bacteria and cells), and biomolecular interactions (drug-receptor, protein-protein, protein-DNA, protein-cell).
Keywords: povrchová plasmonová rezonance; nukleové kyseliny; Surface Plasmon Resonance; Nucleic Acids; mikroskopie; Animals; Protein Interaction Mapping; Proteins; Equipment Design; lidé; design vybavení; proteiny; Bacteria; Humans; mapování interakce mezi proteiny; zvířata; Microscopy